Profil hasil pemeriksaan OAE high noise pada pasien tinnitus di klinik elektromedik RSA UGM - Bawono, Mahatma Sotya; Akuntanto, Ignatius Adhi; Avidati, Herfis; Hapsari, Widiarahma; Sari, Shinta Kusumalarna Sari (Oto Rhino Laryngologica Indonesiana, 2024)
Background: Tinnitus is a hearing disorder in the form of sound sensation without externalstimulation. It can affect a person’s quality of life. The number of patients with tinnitus is expected toincrease. Not many hospitals have a High Noise Otoacoustic Emission (OAE) device for examining tinnitusin patients. Tinnitus research is still limited in Indonesia, especially in Yogyakarta. Purpose: This studyaimed to describe the results of the OAE High Noise examination in tinnitus patients at the ElectromedicalClinic of UGM Academic Hospital. Method: A non-experimental study with a descriptive observationalapproach using secondary data. The sampling technique used was a total sampling technique of tinnituspatients who were examined for (OAE) High Noise from January 1st, 2019, to December 31st, 2021. Result: Respondents who met the inclusion and exclusion criteria were 292 subjects. Most respondentswere more than 60 years old (27.05%), and female (51.71%). The OAE High Noise examination resultsshowed that most of them were abnormal (85.61%). Most of the respondents experienced bilateral tinnitusand experienced disturbances in more than six frequencies (46.60%). The primary diagnosis that had beenfound in the respondents was tinnitus (87.67%). Conclusion: The OAE High Noise examination resultsat the Electromedical Clinic of UGM Academic Hospital were mainly abnormal.